The Pathways from Cyberostracism, Dispositional Hope, and Self-efficacy to Psychological Well-being among University Students: A Serial Mediation Study - Osman Hatun (e-Kafkas Eğitim Araştırmaları Dergisi)
The phenomenon of cyberostracism, characterized by exclusion and being ignored in virtual environments, can negatively impact mental health. Previous research has not adequately explored the impact of cyberostracism on well-being or the role of potential mediating variables in this relationship. Examining these mediating pathways can enhance our understanding of how cyberostracism affects individuals' psychological well-being and may inform intervention strategies to mitigate its negative effects. This study aimed to investigate the links between cyberostracism, dispositional hope, self-efficacy, and psychological well-being. The participants consisted of 322 college students aged 18 to 40 (M = 21.14, SD = 2.56), selected using a convenience sampling method. Structural Equation Modeling (SEM) and bootstrap analysis were employed to explore how hope and self-efficacy might mediate the link between cyberostracism and psychological well-being. The results indicated that cyberostracism, dispositional hope, self-efficacy, and psychological well-being were significantly associated with one another. Furthermore, SEM and bootstrap analyses showed that dispositional hope and self-efficacy significantly mediated the link between cyberostracism and psychological well-being. In conclusion, the findings suggest that dispositional hope and self-efficacy may mitigate the adverse impact of cyberostracism on psychological well-being. These results may contribute significantly to counseling practices and educational research aimed at supporting college students' psychological well-being and preventing the negative effects of cyberostracism.